Pengaturan Tentang Gencatan Senjata Dalam Hukum Humaniter Internasional - Renyut, Sintia Elisabeth; Rehatta, Veriana Josepha Batseba; Leatemia, Wilshen (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The ceasefire between Israel and Hamas will begin on Friday (21/5/2021) at 02.00 local time. The ceasefire ended tensions that had existed in Gaza since 11 days ago. The ceasefire, has the potential to prevent the fiercest fighting in decades. The Israeli military also unanimously supports a ceasefire in Gaza.Purposes of the Research: To review and analyze the Armistice Regulations Formulated in International Humanitarian Law and to study and analyze the legal consequences of violations of the Armistice.Methods of the Research: Legal research as a process to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues faced. Normative legal research or other names, namely doctrinal legal research, is research that provides a systematic explanation of the rules governing a certain category, analyzes a relationship between regulations, explains regions and may predict future development. Results of the Research: The results of this study explain that the armistice is a temporary cessation of war, where both parties involved in the armed conflict both agree or agree to a ceasefire. General arrangements for an armistice were regulated in the Hague Convention of 1907 and contained in the Hague land war regulations. The legal consequences of the violation of the truce are, in accordance with the provisions of Article 41 of the Hague Convention IV of 1907 which states that